Wisdom in the Jewish and Christian Scriptures: Wisdom in the New Testament - Thiselton, Anthony C. (Theology, 2011)
Wisdom in James denotes not intellectual cleverness but a practical gift from God for everyday life, especially in the face of trials. Parallels exist in Judaism and Stoicism. In the Gospels wisdom often finds expression in short, pithy aphorisms, particularly in ‘Q’ and in pronouncements following parables. Jesus is more, but not less, than a wisdom-teacher. Examples are considered. In Corinth wisdom had become a status-seeking commodity. Hence Paul speaks of the wisdom of God and of the cross. In the Pauline epistles wisdom has Christological significance.